2012
DOI: 10.1007/s12046-012-0092-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of burnishing parameters and determination of select surface characteristics in engineering materials

Abstract: The present study is aimed at filling the gaps in scientific understanding of the burnishing process, and also to aid and arrive at technological solutions for the surface modifications based on burnishing of some of the commonly employed engineering materials. The effects of various burnishing parameters on the surface characteristics, surface microstructure, micro hardness are evaluated, reported and discussed in the case of EN Series steels (EN 8, EN 24 and EN 31), Aluminum alloy (AA6061) and Alpha-beta bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In earlier studies of the ball burnishing process, the Taguchi method [43][44][45][46][47][48][49][50] and response surface methodology (RSM) [51][52][53][54][55][56] were widely used. The Taguchi method reduces the number of experiments required for analysis but considers only the main effects on the process and does not allow consideration of the interaction between the input variables.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies of the ball burnishing process, the Taguchi method [43][44][45][46][47][48][49][50] and response surface methodology (RSM) [51][52][53][54][55][56] were widely used. The Taguchi method reduces the number of experiments required for analysis but considers only the main effects on the process and does not allow consideration of the interaction between the input variables.…”
Section: Introductionmentioning
confidence: 99%
“…A roughness of 0.055 μm and hardness of 46.69 HRC for the burnished T215Cr12 material were obtained with the aid of the response surface method [2]. Babu et al [3] stated that the burnishing depth significantly increased the micro-hardness, while the average roughness was primarily influenced by the burnishing force for the burnishing processes of the EN steels, aluminium alloy, and alpha-beta brass. Tadic et al [4] emphasized that a small burnishing force significantly contributed to a lower roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Babu et al. 17 reported the effects of burnishing parameters on the surface characteristics, microstructure and microhardness. Based on optimal burnishing parameters, they presented burnishing maps.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that burnishing with an especially designed tool improved ductility but did not improve hardness. Babu et al 17 reported the effects of burnishing parameters on the surface characteristics, microstructure and microhardness. Based on optimal burnishing parameters, they presented burnishing maps.…”
Section: Introductionmentioning
confidence: 99%